Dynamic Simulation Model of Garlic Availability in Bali Using iThink Software - Hafizi, Muhamad; Hafiz, Syauqi Abyan; Sugiharto, Bambang; Tosida, Eneng Tita; Subandi, Kotim; Sugara, Victor Ilyas (Operations Research: International Conference Series, 2025)
Fluctuations in local production, increasing demand, and dependence on garlic supplies from outside the island make it difficult for Bali Province to maintain a stable garlic supply. iThink software is used to model the dynamic garlic availability system in this study. This simulation method involves creating a Causal Loop Diagram (CLD), creating a mathematical model based on differential equations, and conducting table and graphical analysis of the simulation results. The simulation results show that the linear increase in garlic demand of 6,289.08 tons per year can be offset by local production increasing to 31,071.73 in 2024 and an off-island supply of 4,176 tons per year. The projection of garlic availability until 2024 is 122,895.71 tons. The results show that maintaining a stable supply of off-island garlic is the main way to ensure sustainable garlic availability in Bali.